Pertunjukan Tari Dikee Pam di Desa Tuwi Eumpeuk Kecamatan Panga Kabupaten Aceh Jaya - Yeni Zuryaningsih; Cut Zuriana; Yosi Julia Nanda; Naura Atkiya (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research discusses the traditional dance Dikee Pam from Tuwi Eumpek village, Panga subdistrict, Aceh Jaya Regency, which has become one of the cultural heritage of Indonesia. The Dikee Pam traditional dance has been transformed from religious rituals into a performing art by having 16 likkok or movement variations and 16 male players and 2 radat. The basis of this research is motivated by the importance of preserving the traditional Dikee Pam dance. The main focus of the research is the performance, history, development, function and efforts to preserve Dikee Pam. This dance originally functioned as a ritual to celebrate the birthday of the Prophet Muhammad and has now developed into a performing art form that is performed at various official and entertainment events. The research method is a descriptive approach using interviews, observation and documentation. The results showed that interest in Dikee Pam is declining due to lack of financial support and lack of interest among the younger generation, which is the main challenge to its preservation. However, the local community is still trying to preserve this dance through the Aneuk Nanggroe studio. This research recommends the importance of documentation, integration into local education and the development of Dikee Pam as a potential cultural tourism to maintain sustainability,